The effect of Cornus mas fruit extract consumption on lipid profile, glycemic indices, and leptin in postmenopausal women— A randomized clinical trial. (16th August 2019) - Gholamrezayi, Afsane; Aryaeian, Naheed; Rimaz, Shahnaz; Abolghasemi, Jamileh; Fallah, Soudabeh; Moradi, Nariman; Taghizadeh, Mohsen
Abstract : Menopause, which occurs following a declined ovarian activity and reduced estrogen levels, can lead to long‐term changes in lipid and glycemic profiles and increases the risk of cardiovascular disease and osteoporosis. Cornelian cherry ( Cornus mas ) is rich in phytochemicals and antioxidants, which appears to be useful in reducing the postmenopausal complications. This interventional, double‐blinded, randomized clinical trial carried out on 84 menopaused women aged 45–60 years old. They were randomly divided into two groups. The treatment group received three capsules of 300 mg of Cornus mas extract (CME), and control group received three capsules of 300 mg of starch powder per day for 8 weeks. Then, BMI, waist circumference, glycemic indices, lipid profile, serum apoproteinase, apoprotein B100, fibrinogen, and leptin were measured. The dietary intakes were evaluated using 24‐hr dietary recall questionnaire. The consumption of CME in comparison with the control group resulted in a significant reduction in weight, body mass index, waist circumference, LDL to HDL ratio, total cholesterol to HDL ratio, and fibrinogen. There was also a significant increase in HDL and ApoA1 levels in the treatment group. Furthermore, there was a significant decrease in BMI, waist circumference, fasting insulin, and insulin resistance index after 8 weeks of using CME. Summing up the results, it can be concluded that CME can have possible effects on decreasing BMI, waist circumference, and improving some aspects of lipid profile and glycemic indices in postmenopausal women.